Caracterização estrutural e papel do fator de crescimento derivado de plaquetas (PDGF) na foliculogênese ovariana - Brito, Ivina Rocha; Lima, Isadora Machado Teixeira; Saraiva, Márcia Viviane Alves; Silva, José Roberto Viana; Rodrigues, Ana Paula Ribeiro; Figueiredo, José Ricardo de (Acta Scientiae Veterinariae, 2018)
Background : : : : The platelet-derived growth factor (PDGF) is expressed in a wide variety of cell types, exerts a potent mitogenic role and acts on the growth, differentiation and cell chemotaxis. Studies have shown that during folliculogenesis, PDGF and their receptors are expressed in oocytes, granulosa cells and thecal cells of ovarian follicles at different developmental stages in several species. Although exist many information about its expression sites, as well as about its action in different cells types, the role of PDGF on ovarian folliculogenesis remains understudied. Thus, this article aims to review issues related to PDGF, suggesting the involvement of this mitogenic factor during follicular development. Review: Along this work, it was shown aspects related to structural characterization of PDGF and its receptors, as well as PDGF expression in different cells types, emphasizing its importance to follicular development. PDGF family is composed by four polypeptide chains (each encoded by a different gene), which are synthesized in the form of inactive pro-proteins. After a proteolytic processing, these chains undergo homo or heterodimerization, resulting in five isoforms (PDGF-AA, -BB, -AB, -CC e -DD). The cellular effects of these different PDGF isoforms are mediated by binding, with different specificities, to three transmembrane receptors isoforms of type tyrosine kinase generated by the association of subunits ? e ? (PDGFR- ??, - ??, - ??). PDGF was initially purified from platelets, being later verified its production by many varieties of cell types. It acts as an important mitogenic factor, especially to cells of mesenchymal origin as fibroblasts and smooth muscle cells, and also exerts a role on cellular migration and survival. Studies with PDGF and its receptors have demonstrated its importance as a paracrine growth factor for normal embryo development and angiogenesis. Although the action of this growth factor has been shown in several cellular responses, its role in ovarian folliculogenesis of mammals is understudied. Folliculogenesis, event initiated at pre-natal life in most species, can be defined as the process of follicular formation, growth and maturation, beggining with the primordial follicle formation and resulting in preovulatory stage. Until the present moment, the different PDGF types and their receptors were detected in ovarian follicles of murines, rodents, swines and humans according to developmental stage. Evidences suggest that this growth factor may acts as a potent regulator of ovarian function, increasing DNA synthesis in granulosa cells and stimulating theca cells growth in swines. In addition, PDGF has shown benefic effects in in vitro maturation of bovine oocytes when associated with follicle stimulating hormone (FSH). Conclusion: Nevertheless, the specific actions of PDGF on ovarian follicles development have not been described due to lack of data available in the literature about this subject. Therefore, this review was performed to clarify the involvement of this growth factor in the regulation of ovarian function in mammals. However, it is necessary to perform additional studies that may provide a greater understanding about the importance of PDGF during folicullogenesis.